Flow structure in modern cities: wind tunnel investigation - Farhana Najwa Azman; Lotfy, Eslam Reda; Ashraf Amer Abbas; Zambri Harun (Penerbit Universiti Kebangsaan Malaysia, 2018)
Natural ventilation dominates the heat dissipation and pollutant dispersion in modern cities. Investigations into the flow structure and urban heat island in the Kuala Lumpur City Centre (KLCC) have been conducted by a few researchers. However, these studies were mainly accomplished by means of computational fluid dynamics. The critical problem with computational analysis is the lack of verification. As such, in this research, experimental tools such as the wind tunnel, hotwire anemometry, Pitot tube, and pressure and temperature sensors were utilized. The aim was to assess the ventilation performance of different city models with a height-to-width ratio that was similar to that of the KLCC. Several steps had to be performed before starting the study, among these being the building of the model. A 6×6 array of uniform acrylic blocks (50×50×100 mm) were arranged in line at equal distances. Three arrangements, representing different building densities (35, 25 and 15 %), were examined in the current research. The freestream wind speed was fixed at 5 m/s. The flow was found to be comprised of vortical structures, and attained an energetic turbulence in the downstream of the building areas as compared to the free flow areas. This study suggests keeping the plane area ratio in high-rise building cities within a 15-25% range. The study is beneficial to town planners as the construction of more skyscrapers is being planned.